2017
DOI: 10.1038/bjc.2017.257
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive geriatric assessment in 326 older women with early breast cancer

Abstract: Background:One-third of new early breast cancer diagnoses occur in women over 70 years old. However, older women are less likely to receive radical curative treatments. This study prospectively evaluated a cohort of older women using a Comprehensive Geriatric Assessment (CGA) to determine whether fitness explained the apparent under-treatment in this patient group.Methods:In this multi-centre prospective study, patients aged ⩾70 years with Stages I–III breast cancer underwent a pretreatment baseline CGA consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 40 publications
(33 reference statements)
3
21
0
Order By: Relevance
“…But recent population data indicate that OS for BC in older patients improves with adjuvant RT . The heterogeneity of the elderly population also complicates the choice of the most appropriate treatment for such patients . In this oncological scenario, there is a paucity of published data on the safety and efficacy of Hypo‐RT in relation to the impact of aging and comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…But recent population data indicate that OS for BC in older patients improves with adjuvant RT . The heterogeneity of the elderly population also complicates the choice of the most appropriate treatment for such patients . In this oncological scenario, there is a paucity of published data on the safety and efficacy of Hypo‐RT in relation to the impact of aging and comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Irrespective of the purpose of the CGA, patients with increasing age were more likely to be described as unfit or frail [37,38], and had poorer survival and breast cancer treatment outcomes [38e40]. Two prospective studies evaluated whether routine CGA altered breast cancer treatment decisions [41,42] and reported different findings. In the study by Okonji et al, women defined as unfit or frail were less likely to undergo surgery or receive adjuvant chemotherapy [42].…”
Section: Tools For Identifying Frailty In Patients With Breast Cancermentioning
confidence: 99%
“…Two prospective studies evaluated whether routine CGA altered breast cancer treatment decisions [41,42] and reported different findings. In the study by Okonji et al, women defined as unfit or frail were less likely to undergo surgery or receive adjuvant chemotherapy [42]. In contrast, Barth el emy et al reported that the CGA results did not influence multi-disciplinary team (MDT) decisions on adjuvant chemotherapy [41].…”
Section: Tools For Identifying Frailty In Patients With Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations